Changes in Ethylene and Total Nonstructural Carbohydrates Content in Stem Apex Prior to Leaf Flushing of Marian Plum (Bouea burmanica Griff.) cv. Toon Klaow - Ladawan Lerslerwong; Tanart Thunyarpar; Suranant Subhadrabandhu (Agriculture and Natural Resources, 2002)
Changes in ethylene and total nonstructural carbohydrate (TNC) content in stem apex prior to leaf flushing of marian plum (Bouea burmanica Griff.) cv. Toon Klaow were studied. It was found that ethylene concentration in the intercellular space was low and remained constant between the 4th to the 1st week prior to leaf flushing but the level increased to the maximum at leaf flush. Whereas, the TNC content reached the maximum level at the 4th week before leaf flushing, then decreased linearly to the minimal level at the week of leaf flushing.